The identity of emigrants from Mexico City - SABATES, Ricardo; PETTIRINO, Fabio (Papeles de Población, 2007)
This paper investigates the identity of emigrants from Mexico City and its consequences for adaptation in the City of León. Specifically it describes how identities are formed, investigates the origins, uses, and possible connotations of identity names of migrants from Mexico City and locals from Leon.  Our findings suggest that although there are common identity elements between internal migrants and locals, the interaction between them brought up differential aspects of their identity in terms of religious beliefs and work ethics.  The identity name chilango , given to a person from Mexico City, carries a negative connotation and it can create a stereotype and a risk of prejudice. Since a person called this name might face difficulties integrating with the host society, migrants change the stereotyped behaviours attached to such a name.  Therefore, the ability of migrants interviewed in this study to integrate has not been prohibited by an identity-based conflict with locals, but integration has required facing negative stereotypes and prejudice attached to a person from Mexico City.